Predicting the Feasibility of Phenol Extraction from Water in Different Solvents Using the NRTL Model and a Genetic Algorithm - Nardjess Bouneb; Mouna Talbi; Amani Elgouacem; Abir Mezen (Chemical Engineering Transactions)
This work aims to predicted the feasibility of extracting phenol from water in four different solvents, based on equilibrium data which has been calculated using the NRTL(Non Random Two Liquid) model at various temperatures and at atmospheric pressure. Liquid-liquid equilibrium modelling leads to a nonlinear objective function that can be minimized using a genetic algorithm which has proven to be very performing in reaching the optimum. The predicted results are in agreement with experimental phase equilibrium data. The partition coefficients values exceed 1, suggesting that the extraction of phenol from water is possible using each of the four solvents studied: naphthalene, an amine, pentanone, and benzene. Among these solvents, pentanone has proven to be the most effective, particularly at a temperature of 303 K, as its partition coefficient is higher than that of the other solvents.